Transforming the Financial Ecosystem: The Synergy of FinTech, RegTech, and Artificial Intelligence - Areiqat, Ahmad Yousef; Al- Aqrabawi, Rowaida (International Journal of Membrane Science and Technology, 2023)
This article explores the applications and implications of FinTech, RegTech, and Artificial Intelligence (AI) within the rapidly evolving financial ecosystem. By evaluating relevant literature and case studies, the article demonstrates the synergy of these three technological domains and critically discusses the challenges and opportunities they present. The paper concludes by outlining key insights and potential directions for future research.